Inconsistencies and Doubtful of World University Rankings - Koto, J; Wijaya, A.A; Putrawidjaja, M (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
University rankings have become a trend to gauge the credibility and quality of the university. The university rating has generated much debate about the usefulness, method and accuracy of the assessment results. There are some institution who issued university rankings such as QS, 4ICU, CWUR and Webometrics. The universities were assessed depending on research indicators and opinion surveys. There are many anomalies in ranking gap values between universities as well some clumsiness of values at certain regions. The inadequacy of those tabulation indicators to assess most universities will look purely for reasons of obvious statistical instability. Statistically, there are three regions of ranking gap values: low, medium and high. Standard deviation of ranking gap values for universities in USA and UK is 6-7, Japan is 16, South Korea is 70, and Singapore, Malaysia and Indonesia are no applicable. Those values indicate inconsistency of judgment and invalid and inaccuracy data used in the assessment.